Young bumblebees may rely on both direct pollen cues and early experience when foraging. Issue 1933 (26th August 2020) - Ruedenauer, Fabian A.; Sydow, David; Spaethe, Johannes; Leonhardt, Sara D.
Abstract : An adequate supply of macro- and micronutrients determines health and reproductive success in most animals. Many bee species, for example, collect nectar and pollen to satisfy their demands for carbohydrates, protein and fat, respectively. Bees can assess the quality of pollen by feeding on it, but also pre-digestively by means of chemotactile assessment. Whether they additionally use larval nutritional experience, as has been shown for Drosophila melanogaster and Bombyx mori, is unknown. In this study, we tested whether pollen selection of bumblebee foragers is affected by nutritional experience (acquired before the onset of foraging) or solely by food quality. Bumblebee larvae were fed with one out of three different pollen blends. As adults, they were offered all three blends when they started foraging for the first time. We found all treatment groups to prefer one out of the three blends. This blend provided the highest nutritional quality and increased the bees' lifespan, as shown by feeding studies with microcolonies. Besides, bees also chose the pollen blend fed during their larval stage more often than expected, indicating a significant effect of pre-foraging experience on adult pollen foraging behaviour. The combination of both direct pollen quality assessment and pre-foraging experience (i.e. during the larval phase or as early imagines) seems to allow foraging bumblebees to efficiently select the most suitable pollen for their colony.